Thaw and Armenian Painting: Рages of Art Criticism of the 1950s - Sargsyan, Lilit H. (Actual Problems of Theory and History of Art, 2024)
The article is the first to examine the significance and characteristics of the Khrushchev Thaw transformations in Armenian painting. The main source material is derived from the press of the period under investigation. The author draws attention to the formation of a new conjuncture in Soviet painting and art criticism during the 1950s, which corresponded to the Khrushchev’s reforms and their associated propaganda, as well as the opposition of Armenian artists to this conjuncture. A special attention is paid to totalitarian methods of art management and their criticism, which became possible as a result of the reforms, the general directions of art democratization, as well as the national policy regarding the art of Soviet peoples. The article is based on the analysis of a large-scale exhibition of Armenian fine art, held in June 1956 in Moscow as a part of the Decade of Armenian art and literature and, in particular, two eminent Thaw paintings which became the revelation of the exhibition: “Spring” by Hovhannes Zardaryan and “Komitas. Last night” by Sargis Muradyan. By their example, the author identifies two main directions in the renewal of Armenian painting of the Thaw period as purely artistic and thematic. The author comes to the conclusion that after the Stalinist restrictions, the revival of Armenian Soviet painting of the second half of the 20th century was not so much a direct consequence of the Thaw, but rather the continuation of its pre-revolutionary national and European artistic traditions.
Keywords: art and totalitarian regime; Khrushchev’s Thaw; Khrushchev’s reforms and painting; Armenian painting; second half of the 20th century; Decade of Armenian Art and Literature in Moscow; 1956; Hovhannes Zardaryan; Sargis Muradyan; Armenian Genocide of 1915; national features in Soviet Armenian art